2017
DOI: 10.3390/molecules22060773
|View full text |Cite
|
Sign up to set email alerts
|

New Mild and Simple Approach to Isothiocyanates: A Class of Potent Anticancer Agents

Abstract: In our current work, acetyl chloride-mediated synthesis of phenethyl isothiocyanate (PEITC) derivatives proves to be convenient and provides the expected products at good to excellent yields. Biological evaluation and structure-activity relationship analysis found that the novel compound 7 showed the best anticancer activity against human cancer cell line Panc1 and HGC27 compared with PEITC. Compounds 6 and 7 induced more apoptosis in pancreatic cancer cells but less toxicity in non-cancer cells. Further biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“… 30 1a–c were then converted to 4a–c via an azidation and reduction reaction. Finally, the intermediates 4a–c bearing an amino group reacted with carbon disulfide (CS 2 ) in dried THF 31 to afford the target compounds 5a–c. All the synthesized compounds were purified by silica gel column chromatography.…”
Section: Resultsmentioning
confidence: 99%
“… 30 1a–c were then converted to 4a–c via an azidation and reduction reaction. Finally, the intermediates 4a–c bearing an amino group reacted with carbon disulfide (CS 2 ) in dried THF 31 to afford the target compounds 5a–c. All the synthesized compounds were purified by silica gel column chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Isothiocyanates, major compounds of cruciferous vegetables, have been widely known to have cancer prevention effects [41]. Luo et al showed that Methyl4-(2-isothiocyanatoethyl) benzoate (compound 6) and N-Ethyl-4-(2-isothiocyanatoethyl) benzamide (compound 7) especially had a more apoptotic effect in PANC-1 but were less noxious to non-cancer cells.…”
Section: Natural Compounds From Plantsmentioning
confidence: 99%
“…As a result, the rate of apoptotic cell death increased after treatment, mostly in a dose-and time-dependent manner. Chaetospirolactone, xylarione A, (-) 5-methylmellein, 2 ,4 -Dihydroxy-6 -methoxy-3 ,5 -dimethylchalcone (DMC), 3,5-dihydroxy-6,7,8-trimethoxyflavone (flavone B), 5,7dihydroxy-3,6,8-trimethoxyflavone (Flavone A), cardiac glycosides, elemene, hydroxychavicol, hypoxoside, mastic gum resin (MGR), Methyl4-(2-isothiocyanatoethyl)benzoate (compound 6), monogalactosyl diacylglycerol, N-Ethyl-4-(2-isothiocyanatoethyl)benzamide (compound 7), piperlongumin, RN1, withaferin A, bitter apricot ethanolic extract, Eucalyptus microcorys aqueous extract (F1), and Salvia chinensis polyphenol-rich extrac, showed almost no cytotoxicity in normal cells while having an apoptotic effect on pancreatic cancer cells [24,26,29,30,32,36,38,39,[41][42][43][44]46,49,51,55,62]. The rest of the studies on the apoptosis of pancreatic cells did not handle experiments on normal cells, so additional tests are required.…”
Section: Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, heterocyclic fragments are good candidates. We are interested in seeking compounds exhibiting antiproliferative ability against malignant cancers by targeting tumorigenic pathways . In the past, a series of heterocycles containing a biaryl system were made in our laboratory .…”
mentioning
confidence: 99%